Determining the Secondary Role of UV Light in Swimmers Melanoma Genesis - A. Embi, Abraham (New Visions in Biological Science Vol. 8, 2022)
Background: Swimmers have a greater risk of cutaneous melanoma than non-swimmers. Experimental investigations have been unable to explain why ultraviolet radiation (UV) is the sole cause of cutaneous melanomas in swimmers. Several writers have proposed different mechanisms as etiological factors, including the incidence of hydrogen peroxide (H2O2) decomposition in hair follicles. H2O2 produced by keratinocytes, for example, diffuses into melanocytes and may have a role in the aetiology and pathogenesis of cutaneous melanoma. Other in vitro investigations show that in water submerged hairs, sites such as the infundibulum and at wounded hair follicles is where exogenous H2O2 could penetrate. The energy released by catalase during the decomposition of H2O2 in the eukaryotic cell has also been proposed as a factor in the development of cancer. Consumption of the seaweed Sargasum filipendula, which has antiproliferative and antioxidant characteristics, has been linked to a lower incidence of Melanoma genesis in nations like Japan, according to epidemiological research. H2O2 appears to be the missing attributable risk in swimmers' cutaneous melanomas according to this paper. Methods: A literature survey was performed, which aimed to identify exogenous H2O2 as a key factor in the causation in cutaneous swimmers Melanoma genesis. Results: All published theories and actual in vitro experiments in Swimmers identify H2O2 as essential factors for cutaneous melanoma. Exogenous H2O2 can enter the human hair follicle through two sites in water-submerged hairs: the hair shaft/skin junction and sites where the external follicular wall has been damaged by injury. Conclusion: According to published data, the incidence of cutaneous melanomas in swimmers is higher than in the general population. H2O2 forms by the conversion of dissolved organic matter by the sun UV light in fresh or salt-water bodies. In Swimmers, spontaneously penetrating into the hair follicles. Proposed is that Melanoma tumour cells are then formed as a result of catalase decomposition of H2O2, and the malignant cells spread into the surrounding tissues. UV light from the sun is thought to play a secondary role, with H2O2 being the primary attributable risk.